(untitled) (International Journal of Engineering and Computer Science, 2014)
Teaching is the process of carrying out the activities which is effective in getting students to learn. The cognitive knowledge of every student in a classroom is not uniform. Some students are good at reasoning and some are not. This paper suggests aligning the questions in the question paper of periodical tests with Bloom’s Taxonomy. Assess the answer script of each student and categorize them using K-Means Clustering algorithm under different levels of the Bloom’s Taxonomy. This activity helps lecturer to get the reasoning strength of each student in a classroom. The lecturer can put more attention to improve intellectual skills of students having weak reasoning power. The aim of this paper is to improve the students’ performance through enhancing their ability.